Non-production benefits of education: Crime, health, and good citizenship - Lance Lochner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2010)
Economists have long recognized and measured the effect of education on an individual's own lifetime earnings. More recently, attention has been paid to the effects of education on other personal and social outcomes, such as criminal behavior, health and mortality, and voting and democratic participation. A growing body of work suggests that education offers a wide-range of benefits that extend beyond increases in labor market productivity. This chapter reviews recent developments on these 'non-production' benefits of education with an emphasis on contributions made by economists.
Keywords: 330; Bildungspolitik; Bildungsinvestition; Kriminalität; Gesundheitsvorsorge; Gesellschaftliches Bewusstsein; Demokratie; Welt